Meningkatkan Hasil Belajar Siswa pada Materi Membangun Hidup yang Bermartabat Melalui Model PBL pada Fase F Kelas XI DI SMKN 1 Sintang - Jemai Jemai; Nerita Setyaningtiyas (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This research aims to improve student learning outcomes at SMKN 1 Sintang through the implementation of a Problem-Based Learning (PBL) model. The background of this research is based on the problem of the low success rate of students in the conventional or lecture-based learning process, which is characterized by low active participation of students and a lack of understanding of the material on building a dignified life. This research used a Problem-Based Learning (PBL) model involving 22 students from different majors in Phase F. The results of the research indicate that the application of PBL significantly improved student learning outcomes compared to the old or lecture-based teaching method. In addition, the PBL model was also proven effective in increasing student motivation, participation, engagement, and interest throughout the learning process. Thus, the application of PBL is recommended as a learning strategy that can improve student learning success at SMKN 1 Sintang, specifically in the Catholic Religious Education subject on the material of Building a Dignified Life.